Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3791/51185
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Ice-binding Planes of Antifreeze Proteins by Fluorescence-based Ice Plane Affinity

Abstract: Antifreeze proteins (AFPs) are expressed in a variety of cold-hardy organisms to prevent or slow internal ice growth. AFPs bind to specific planes of ice through their ice-binding surfaces. Fluorescence-based ice plane affinity (FIPA) analysis is a modified technique used to determine the ice planes to which the AFPs bind. FIPA is based on the original ice-etching method for determining AFP-bound ice-planes. It produces clearer images in a shortened experimental time. In FIPA analysis, AFPs are fluorescently l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 33 publications
6
76
0
Order By: Relevance
“…Similar shaping and burst patterns have been seen for other hyperactive IBPs able to bind to the basal plane of ice [40]. To confirm basal-plane binding of SfIBP_1 IBD, Fluorescence-based Ice Plane Affinity (FIPA) analysis was undertaken, incubating macro-scale hemispheres of single ice crystals with FITC-labelled IBP [21,23,41]. Even after scraping off the outer most surface of the ice to remove any nonspecific binding, the entire ice hemisphere fluoresced, indicating that the SfIBP_1 IBD binds to multiple planes of ice, including the basal plane ( Fig.…”
Section: Sfibp_1 Duf3494 Confirmed As An Ice-binding Protein With Hypmentioning
confidence: 68%
See 2 more Smart Citations
“…Similar shaping and burst patterns have been seen for other hyperactive IBPs able to bind to the basal plane of ice [40]. To confirm basal-plane binding of SfIBP_1 IBD, Fluorescence-based Ice Plane Affinity (FIPA) analysis was undertaken, incubating macro-scale hemispheres of single ice crystals with FITC-labelled IBP [21,23,41]. Even after scraping off the outer most surface of the ice to remove any nonspecific binding, the entire ice hemisphere fluoresced, indicating that the SfIBP_1 IBD binds to multiple planes of ice, including the basal plane ( Fig.…”
Section: Sfibp_1 Duf3494 Confirmed As An Ice-binding Protein With Hypmentioning
confidence: 68%
“…3A), which showed that TH activity increased steeply at low IBP concentrations and approached a plateau below 2°C at 80 lM. To confirm basal-plane binding of SfIBP_1 IBD, Fluorescence-based Ice Plane Affinity (FIPA) analysis was undertaken, incubating macro-scale hemispheres of single ice crystals with FITC-labelled IBP [21,23,41]. The level of activity displayed by SfIBP_1 IBD falls somewhere in between the easily identifiable moderate and hyperactive designations, as seen through comparison with the moderately active LeIBP, which demonstrates activity well below 0.5°C even at 100 lM, and the hyperactive FfIBP, which approaches a plateau in TH activity at 3°C, a full degree higher than that obtained with SfIBP_1 IBD, and at a much lower protein concentration (Fig.…”
Section: Sfibp_1 Duf3494 Confirmed As An Ice-binding Protein With Hypmentioning
confidence: 99%
See 1 more Smart Citation
“…Midge AFP was labelled with FITC as described previously for labelling with tetramethylrhodamine isothiocyanate (TRITC) . FIPA analysis was performed using 1.5 mg of midge AFP in 30 mL of working buffer as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…85,99 The regions where IBPs accumulate appear upon . 100 Prior to such a fluorescence based ice-plane affinity (FIPA) assay, IBPs are either coupled to a fluorescent dye or to a fluorescent protein in a fusion protein construct.…”
Section: E Ice Plane Affinity Analysismentioning
confidence: 99%